Reports of cohesion and manifestation of the madness social imaginary by family members and users of mental health at the time of admission - Belisa Vieira da Silveira; Amanda Márcia dos Santos Reinaldo (Universidad de Antioquia, 2016)
Objective. To understand the social imaginary of madness and its manifestation at the time of referral to hospitalization of users of mental health by their families. Methods. Case study, qualitative, conducted in a mental health service in the city of Belo Horizonte, Brazil. Data collection was through non-participant observation and interviews with semi-structured to eight service users. Data were analyzed using content analysis proposed by Bardin. Results. The results indicate that the mad man speech is still denied and has no space due to the social imaginary of madness. Therefore, the hospital appears as a solution for the family, since they do not understand the mental illness process, designing the patient as bum. Since the mad man speech is not recognized, the family's demand prevails and becomes coercive. Conclusion. The conclusion of this study is that the social imaginary of madness is still associated with unreason and social inadequacy of the subject in psychological distress, which leads families to choose the hospital psychiatric hospitalization.   How to cite this article: Silveira BV, Reinaldo MAS. Reports of cohesion and manifestation of the madness social imaginary by family members and users of mental health at the time of admission. Invest. Educ. Enferm. 2016; 34(3): 502-510